Accelerated Stress Testing by Rotating Disk Electrode for Carbon Corrosion in Fuel Cell Catalyst Supports. Issue 7 (1st January 2015) - Riese, Adam; Banham, Dustin; Ye, Siyu; Sun, Xueliang
Abstract : Durability is one of the key remaining challenges to widespread adoption of proton exchange membrane fuel cells (PEMFCs). The durability and continued high performance of a PEMFC using carbon supported catalysts is highly dependent on the stability of the carbon support. Presently, there are a multitude of accelerated stress test (AST) protocols using rotating disk electrode (RDE) voltammetry to study the corrosion of carbon catalyst support materials, though it remains unclear whether all of these tests provide meaningful reproduction of in-situ membrane electrode assembly (MEA) test results. We evaluate two carbon corrosion ASTs and compare results to MEA data for three well known carbon supported catalysts. Physical characterization of each carbon type by gas sorption, XRD, and Raman, is used to elucidate the observed trends in corrosion resistance and the effects of testing temperature, scan rate, and upper potential limit are examined. We find that AST results are highly dependent on temperature and total testing time, concluding that the first protocol is only valid at 60°C, while the second accurately represents MEA data. This study highlights the importance of different RDE AST parameters when developing ASTs that correlate with in-situ MEA testing.